Driving Digital Banking Transformation in Indonesia Amid Industry 4.0 - Teguh Joni Purwanto; Triwidi Atmoko; Susilo Toto Rahardjo (Arthatama: Journal of Business Management and Accounting, 2025)
The study emphasizes the role of regulatory frameworks and government initiatives in accelerating digital transformation within the banking sector. The Indonesian Financial Services Authority and Bank Indonesia have introduced various policies to support innovation while ensuring consumer protection and financial system stability. In addition, the research explores how customer behavior is shifting toward digital channels, driven by convenience, speed, and accessibility. This behavioral shift necessitates banks to invest in user-friendly digital platforms and robust IT infrastructure. The study also discusses the importance of digital literacy among consumers and employees to maximize the benefits of digital banking. Moreover, collaboration between traditional banks and fintech companies is identified as a key strategy to foster innovation and expand financial inclusion. By addressing both opportunities and risks, this research provides a comprehensive perspective on how Indonesian banks can effectively implement digital transformation strategies. The insights gained are expected to guide policymakers, financial institutions, and stakeholders in shaping a resilient and inclusive digital banking ecosystem.